PENGARUH KOMISARIS INDEPENDEN DAN KUALITAS AUDIT TERHADAP TAX AVOIDANCE PADA PERUSAHAAN SEKTORLQ45 YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE TAHUN 2014-2018 - Monica Tamara; Rudy Hedianton Saragih (Jurnal Akuntansi dan Perpajakan Jayakarta, 2021)
This study aims to test the effect of independent commissioner and audit quality to tax avoidance. Independent variable that used in this study is independent commissioner and audit quality. While the dependent variable in this study is tax avoidance. The population in this study are directors, commissioners, and managers from 45 manufacturing industry companies included in the LQ45 stock index in period 2014-2018. The result of this study showed on the multiple linear regression analysis that the application value of independent commissioner and audit quality to tax avoidance have a constant value of 0,337. Independent commissioner has negative relationship direction towards tax avoidance of 0,003, however the relationship isn’t significant because 0,003 < 0,023 which is significant value from independent commissioner. Audit quality has positive relationship direction towards tax avoidance of 0,001, however the relationship isn’t significant because 0,001 < 0,043 which is significant value from audit quality. Based on the result of the study, it means that the greater the proportion of independent commissioner, the practice of tax avoidance will decrease. The greater the quality of audit, the practice of tax avoidance will increase.